2015
DOI: 10.5604/12321966.1185773
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to Encephalitozoon cuniculi in European hares (Lepus europaeus)

Abstract: Introduction and objectives. Encephalitozoon cuniculi is an obligate intracellular parasite infecting especially domestic rabbits; however, spontaneous infections have been documented in other mammalian species such as dogs, cats, rabbits, horses, cows and sheep all over the world. Encephalitozoonosis is a chronic and latent disease leading to renal failure, encephalitis, disorders of brain and urinary tract, and may lead to death. There are limited reports on encephalitozoonosis in wildlife, which is why the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Wild species have been considered as potential reservoirs of infections to domestic animals and even humans, based on serological studies. Therefore, antibodies against E. cuniculi have been detected in several wild carnivores, such as the red fox ( Vulpes vulpes ) (Meredith et al 2015 ), the arctic/blue fox ( Alopex lagopus ) (Hersteinsson et al 1993 ; Akerstedt 2002 ), and the feral mink ( Mustela vison ) (Hersteinsson et al 1993 ), but also in wild lagomorphs like European hares ( Lepus europaeus ) (Bártová et al 2015 ; Özkan et al 2021 ). Given the epidemiological results of recent studies, seroprevalence appears to be higher in foxes (52.1%) (Meredith et al 2015 ) than in hares (0.47–2.9%) (Bártová et al 2015 ; Özkan et al 2021 ).…”
Section: Infection In Other Animal Species: Particularities and Poten...mentioning
confidence: 99%
“…Wild species have been considered as potential reservoirs of infections to domestic animals and even humans, based on serological studies. Therefore, antibodies against E. cuniculi have been detected in several wild carnivores, such as the red fox ( Vulpes vulpes ) (Meredith et al 2015 ), the arctic/blue fox ( Alopex lagopus ) (Hersteinsson et al 1993 ; Akerstedt 2002 ), and the feral mink ( Mustela vison ) (Hersteinsson et al 1993 ), but also in wild lagomorphs like European hares ( Lepus europaeus ) (Bártová et al 2015 ; Özkan et al 2021 ). Given the epidemiological results of recent studies, seroprevalence appears to be higher in foxes (52.1%) (Meredith et al 2015 ) than in hares (0.47–2.9%) (Bártová et al 2015 ; Özkan et al 2021 ).…”
Section: Infection In Other Animal Species: Particularities and Poten...mentioning
confidence: 99%
“…identified in wild Lagomorpha. PCR – polymerase chain reaction; H – histology; S – serology.Taxa diagnosed (genotype)Host (scientific name)CountrySubstrateTechniquesReference E. cuniculi European rabbit ( Oryctolagus cuniculus )UKN/AN/AWilson 1979 E. cuniculi European rabbit ( Oryctolagus cuniculus )FranceSChalupsky et al., 1990 E. cuniculi European rabbit ( Oryctolagus cuniculus )AustraliaTissueS, cultureThomas et al., 1997 E. intestinalis , E. hellem European brown hare ( Lepus europaeus )BelgiumTissueH, PCRDe Bosschere et al., 2007 E. cuniculi Cottontail rabbit ( Sylvilagus floridanus )ItalyTissuePCRZanet et al., 2013 E. cuniculi European hare ( Lepus europaeus )Czech Republic, Austria, Slovak RepublicSBártová et al, 2015…”
Section: Encephalitzoon: Species Diagnosis and Transmissionmentioning
confidence: 99%
“…In a recent study in the Czech Republic, Austria and the Slovak Republic 1.42% of European hares ( Lepus europaeus ) were tested positive for E. cuniculi by serology (Bártová et al, 2015). …”
Section: Orders Of Wild Animals Infected With Encephalitozoonmentioning
confidence: 99%
“…It would contribute to the literature by providing up to date information about these diseases which are found in wildlife. Although there are many reports about the importance of encephalitozoonosis in rabbits since 1922, the number of these reports are very limited and the related studies are done with minimal numbers of hares (20,21). Compared to the results of the previous reports, the disease has a high prevalence in domestic rabbits, while with regards to the hare, it had a relatively low prevalence.…”
Section: Discussionmentioning
confidence: 90%
“…infection in domestic rabbits was detected as 15.0% in Egypt ( 22), 16.5% in Nigeria ( 23), 52.0% in The United Kingdom (24), 53% (18) in Turkey and 75.4% in Italy (25). On the other hand, in a recent study, Bártová et al (21) notified that 1.2%, 3.2%, and 4.2% of hares in the Czech Republic, in the Slovak Republic and in Austria respectively, were detected positive for E. cuniculi through serology testing and the total prevalence was found to be 1.42%. However, in Western Australia, Thomas et al (26) reported that 25% of E. cuniculi in hares were found seropositive.…”
Section: Discussionmentioning
confidence: 97%